1998
DOI: 10.1016/s0969-2126(98)00033-1
|View full text |Cite
|
Sign up to set email alerts
|

Copper amine oxidase from Hansenula polymorpha: the crystal structure determined at 2.4 å resolution reveals the active conformation

Abstract: The structure shows TPQ in a position poised for catalysis. This is the first active CAO structure to reveal this conformation and may help further our understanding of the catalytic mechanism. On the substrate side of TPQ a water-containing channel leading to the protein surface can serve as an entrance or exit for substrate and product. On the opposite side of TPQ there is direct access from the bulk solvent of the dimer interface by which molecular oxygen may enter and hydrogen peroxide depart. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
251
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(260 citation statements)
references
References 43 publications
9
251
0
Order By: Relevance
“…HPAO Crystallization-Crystallization was performed as previously reported (13 mg/ml HPAO in 8.0 -9.5% polyethylene glycol 8000, 0.28 -0.30 M phosphate at pH 6.0 at 293 K) with the exception of the use of hanging drop crystallization rather than sitting drop (34). The ratio of protein to well solution in the hanging drops was 1:1, with volumes of 2.5 l, giving a total volume of 5.0 l. The best diffracting crystals were cube-shaped with dimensions of 40 ϫ 40 ϫ 30 m and grew within 3 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HPAO Crystallization-Crystallization was performed as previously reported (13 mg/ml HPAO in 8.0 -9.5% polyethylene glycol 8000, 0.28 -0.30 M phosphate at pH 6.0 at 293 K) with the exception of the use of hanging drop crystallization rather than sitting drop (34). The ratio of protein to well solution in the hanging drops was 1:1, with volumes of 2.5 l, giving a total volume of 5.0 l. The best diffracting crystals were cube-shaped with dimensions of 40 ϫ 40 ϫ 30 m and grew within 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…2) (34,35). The inland lake is conserved at the dimer interface of CAOs and has been suggested as the entry point for O 2 (35).…”
mentioning
confidence: 99%
“…The three-dimensional structure of CuAOs from Escherichia coli (PDB code 1oac; Parsons et al, 1995), Pisum sativum (PDB code 1ksi; Kumar et al, 1996), Arthobacter globiformis (PDB code 1av4; Wilce et al, 1997) and Hanensula polymorpha (PDB code 1a2v; Li et al, 1998) and of the lysyl oxidase from Pichia pastoris (PDB code 1n9e; Duff et al, 2003) have been reported. They all share a similar fold and contain three domains called D2, D3 and D4.…”
Section: Introductionmentioning
confidence: 99%
“…As summarized in a recent review (3), x-ray crystal structures of CAOs have been determined for a number of enzymes from various sources, including bacteria (Escherichia coli (16) and Arthrobacter globiformis (AGAO) (17)(18)(19)), yeasts (Hansenula polymorpha (recently reclassified as Pichia angusta) (HPAO-1 and HPAO-2) (20,21) and Pichia pastoris (lysyl oxidase) (22)), a fungus (Aspergillus nidulans (23)), a plant (Pisum savitum (24)), a mammal (Bos taurus (25)), and Homo sapiens (diamine oxidase and vascular adhesion protein 1, which is identical to semicarbazide-sensitive amine oxidase (26 -28)). The active site structures of these enzymes, including the positions of TPQ and Cu(II), are highly conserved, suggesting that they have a common mechanism for single-turnover TPQ biogenesis and catalytic amine oxidation.…”
mentioning
confidence: 99%